Hybrid bionic RBCM / Zn-MOF nano-drug delivery carrier as well as preparation method and application thereof

By developing FA-RBCM-CuS@ZIF-8 nano drug delivery vehicle, the problem of low drug delivery efficiency in multi-strategy collaborative treatment was solved, efficient delivery and responsive release were achieved, significantly improving the therapeutic effect on breast cancer and reducing the Injury to normal tissue.

CN119424662AActive Publication Date: 2025-02-14HENAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411565821.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

How to develop an efficient nanodrug delivery vehicle that can integrate chemotherapy, photothermal therapy and chemodynamic therapy in multi-strategic synergistic treatment to improve the therapeutic effect on breast cancer while reducing damage to normal tissues.

Method used

Using hybrid bionic RBCM/Zn-MOF nanodrug delivery vector, specifically FA-RBCM-CuS@ZIF-8, CuS NPs and ZIF-8 were synthesized and coated on the surface of RBCM, using FA as a target Modifiers to achieve efficient delivery and responsive release of drugs.

Benefits of technology

It achieves efficient delivery and responsive release of drugs, significantly improves the killing effect on breast cancer cells, reduces the toxicity to normal tissues, and enhances the targeted chemotherapy and the efficiency of collaborative treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424662A_ABST
    Figure CN119424662A_ABST
Patent Text Reader

Abstract

The invention discloses a hybrid bionic RBCM / Zn-MOF nano-drug delivery carrier and a preparation method and application thereof, and relates to the technical field of bionic nano-drug delivery, the nano-drug delivery carrier is FA-RBCM-CuS (at) ZIF-8, and the process comprises the following steps: synthesizing PVP-CuS NPs, mixing 2-methylimidazole and PVP-CuS NPs, adding zinc nitrate hexahydrate, and preparing CuS (at) ZIF-8; the preparation method comprises the following steps: connecting FA to the surface of RBCM to obtain FA-RBCM, mixing the FA-RBCM with CuS (at) ZIF-8, and extruding to obtain the FA-RBCM-CuS (at) ZIF-8 nano-drug delivery carrier. The obtained sample is uniform in particle size distribution and stable in physicochemical property. The carrier is high in DOX encapsulation efficiency and loading capacity, has responsive drug release capacity in a simulated tumor microenvironment, and is good in biological safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of bionic nano drug delivery, and more specifically to a hybrid bionic RBCM / Zn-MOF nano drug delivery carrier and a preparation method and application thereof. Background Art

[0002] Breast cancer is the most common cancer in women worldwide and one of the leading causes of death in women. At present, the clinical treatment of breast cancer mainly includes surgery, radiotherapy and chemotherapy. However, the treatment of breast cancer still faces a series of severe challenges, such as damage to normal tissues, easy recurrence and drug resistance. In order to overcome the defects of traditional treatment methods, the synergy of multiple treatment methods has been explored and proven to be an effective innovative anti-cancer strategy. Multi-strategy synergy can achieve the complementary advantages of various therapies, inhibit tumor growth and proliferation in different mechanisms and ways, and greatly improve the anti-tumor efficacy. Functionalized nanoparticles can be used as carriers for chemical drugs and other diagnostic and therapeutic agents to deliver them efficiently. Compared with traditional chemical drugs, nano drug delivery systems have the advantages of high in vivo bioavailability, good targeting, and controllable drug release capacity.

[0003] Phototherapy is an emerging cancer treatment modality that uses light radiation of different wavelengths to induce photochemical or photothermal changes in target tissues. The most common phototherapy methods include photodynamic therapy (PDT) and photothermal therapy (PTT), which use light and exogenous or endogenous absorbers to generate cytotoxic reactive oxygen species (ROS) or cause local temperature increases, respectively. At the cellular level, both PDT and PTT have been shown to effectively combat drug resistance and compensate for related signaling pathways; in the tumor microenvironment, these two strategies can regulate tumor perfusion, vascularization, and extracellular matrix balance to enhance the efficiency of drug delivery in targeted tumors. In addition, compared with traditional chemotherapy, PDT and PTT provide greater and more precise spatiotemporal control and reduce off-target toxicity. Compared with radiotherapy, phototherapy uses non-ionizing radiation, which reduces the risk of secondary cancer development. In summary, due to its unique mechanism of action and outstanding advantages, phototherapy can be used as an adjuvant for efficient cancer treatment and used in conjunction with traditional therapies.

[0004] ROS-based therapies can target cancer cells or specific organelles, reverse drug resistance, and have strong oxidative lethality. Chemodynamic therapy (CDT) is a new type of cancer treatment method related to ROS. This method reacts with excess intracellular hydrogen peroxide (H2O2) in tumor tissues through Fenton or Fenton-like reactions to produce hydroxyl radicals (·OH). Compared with other types of ROS (such as E(·OH / H2O)=2.17V, E(H2O2 / H2O)=1.78V), ·OH (E(·OH / H2O)=2.80V) as a type of ROS shows stronger oxidative ability and has more powerful tumor cell killing activity. In particular, the production of ·OH does not require O2, but specifically utilizes H2O2 overexpressed in tumor cells. Solid tumors have a special microenvironment of slightly acidic, low oxygen, and high H2O2, and have faster proliferation and metastasis than normal tissues. Therefore, tumor cells overexpressing H2O2 can specifically trigger CDT and reduce possible damage to normal tissues.

[0005] However, the key problem in implementing multi-strategy synergistic therapy is to select the right medium or platform to integrate various therapies. Currently, metal organic frameworks (MOFs) composed of organic ligands and their coordinated metal ions / ion clusters have become a major research hotspot in the biomedical field. Zeolitic imidazolate framework-8 (ZIF-8) is one of the most commonly used MOFs. It is a kind of MOF composed of zinc ions (Zn 2+ ) and 2-methylimidazole, is particularly suitable as a drug carrier for tumor treatment due to its high porosity, adjustable pore size, easy preparation, effective encapsulation / loading of "cargo" from small molecules to biomacromolecules, and responsive biodegradation properties. These advantages also give ZIF-8 excellent performance in mediating a variety of tumor therapies, including chemotherapy, PDT, PTT, CDT, sonodynamic therapy (SDT), starvation therapy, immunotherapy, etc. ZIF-8 has good stability under physiological conditions, and due to the low extracellular pH value, it will disintegrate at the tumor site, achieving responsive drug release, and is a drug carrier with excellent performance. Studies have combined ZIF-8 with other nanoparticles to make composite carrier materials with core-shell structures for multimodal synergistic therapy.

[0006] Red blood cell membrane (RBCM) is a natural long-cycle drug carrier that can be obtained through the hemolysis process. It has become one of the hot spots in the design and research of artificial bionic materials and delivery systems. Studies have shown that the CD47 protein on the surface of RBCM can flexibly transmit signals to macrophages and prevent macrophage phagocytosis. Therefore, coating RBCM on the surface of other nanocarriers can reduce the uptake of the reticuloendothelial system (RES), reduce immune recognition, and prolong the circulation time in the body; at the same time, the RBCM coating can avoid the leakage of loaded drugs, increase the drug concentration in the lesion site, and improve the treatment efficiency. In addition, RBCM has a wide range of sources, low development costs, and great application prospects.

[0007] CuS NPs, as a near-infrared II (NIR-Ⅱ) photothermal conversion agent, has a higher photothermal conversion efficiency than NIR-I photothermal agents. It can rapidly heat up tumor tissue in a short time under NIR-Ⅱ light irradiation. High temperature can cause protein denaturation of tumor cells, inhibit their division and repair process after damage, and then kill them. The warming effect can also promote vasodilation, which can not only increase the amount of O entering the distal hypoxic area, but also increase the amount of oxygen entering the distal hypoxic area. 2 , significantly reducing the hypoxia state in the tumor site, increasing the area of ​​ROS production, and providing enough O2 to the broken DNA to form stable oxygen compounds, preventing the automatic repair of damaged DNA. 2+ It can also catalyze endogenous H2O2 to produce highly cytotoxic ·OH, causing damage to tumor cells, and has strong CDT ability.

[0008] Doxorubicin (DOX) is one of the most commonly used chemotherapeutic drugs in clinical practice, and has excellent inhibitory effects on a variety of solid tumors. Its main mechanism of action is to insert into DNA, destroy topoisomerase II-mediated DNA repair and produce free radicals that cause cell damage, thereby achieving a tumor-suppressing effect. However, long-term use of this drug can bring serious adverse consequences, including cardiac toxicity, bone marrow suppression, etc. These toxic side effects greatly limit the frequency and scope of its use as an anticancer drug. In addition, since DOX does not act specifically on tumor cells, it will be excreted by ABC transporters on the cell membrane after entering the cell, resulting in drug resistance. As a cutting-edge strategy and technology to improve cancer chemotherapy, targeted nanocarriers can enhance the delivery efficiency of drugs such as DOX, reduce toxic side effects, reverse multidrug resistance, and improve the efficacy of chemotherapy.

[0009] Folic acid (FA), also known as vitamin B9, participates in many important biochemical reactions in the body, such as DNA replication and methylation reactions. More importantly, increased FA receptor levels are one of the important biochemical characteristics of various solid tumors. For example, FA receptor overexpression has been found on the surface of epithelial tumor cells in various organs such as breast, colon, lung, prostate, ovary and brain. Therefore, drugs or NPs bound / linked to FA can be rapidly internalized into cancer cells through receptor-mediated endocytosis. In addition, the use of FA as a targeting modifier is believed to bypass the drug efflux pump of cancer cells and alleviate multidrug resistance. Coupled with the non-immunogenic properties of FA, it has more advantages than monoclonal antibodies. Therefore, FA-based targeted therapy is a promising cancer treatment method.

[0010] Therefore, how to provide a hybrid bionic nano drug delivery carrier based on the above materials is an urgent problem to be solved by those skilled in the art. Summary of the invention

[0011] In view of this, the present invention provides a hybrid bionic RBCM / Zn-MOF nano drug delivery carrier and a preparation method and application thereof.

[0012] In order to achieve the above object, the present invention adopts the following technical solution:

[0013] On one hand, an embodiment of the present invention provides a hybrid bionic RBCM / Zn-MOF nano drug delivery carrier, wherein the nano drug delivery carrier is FA-RBCM-CuS@ZIF-8.

[0014] Preferably, the process comprises: (1) synthesizing PVP-CuS NPs;

[0015] (2) Synthesis of CuS@ZIF-8: 2-Methylimidazole was mixed with PVP-CuS NPs, and zinc nitrate hexahydrate was added and mixed again to prepare the pH-responsive nanocarrier CuS@ZIF-8;

[0016] The specific preparation process is as follows: 8 mg of the prepared CuS NPs are weighed and dissolved in 2 mL of methanol and ultrasonically uniformly, 16 mg of the prepared ZIF-8 is weighed and dissolved in 6 mL of methanol and ultrasonically uniformly, the prepared CuS NPs solution is mixed with the ZIF-8 solution, and 6 mL of methanol is added for ultrasonic mixing, stirred at 400 rpm for 5 min at room temperature and then allowed to stand for 2.5 h. After the reaction is completed, centrifuge at 12000 rpm for 20 min in a high-speed centrifuge, collect the precipitate and freeze it in a -80 ° C refrigerator for 12 h, and freeze-dry to obtain the pH-responsive nanocarrier CuS@ZIF-8.

[0017] (3) FA is connected to the surface of RBCM to obtain FA-RBCM, and mixed with the CuS@ZIF-8 prepared in step (2), and extruded to obtain FA-RBCM-CuS@ZIF-8 nano drug delivery carrier.

[0018] Preferably, in step (1), the specific process of synthesizing PVP-CuS NPs is:

[0019] Copper chloride dihydrate and polyvinyl pyrrolidone were weighed in a mass ratio of 1:5, dispersed in ultrapure water, stirred at room temperature for 1 hour, sodium sulfide nonahydrate was added, stirred for 5 minutes, transferred to an oil bath, and heated at 90°C for 40 minutes. After the reaction was completed, centrifuged, the precipitate was collected and freeze-dried to synthesize PVP-CuS NPs; wherein the volume mass ratio of sodium sulfide nonahydrate to polyvinyl pyrrolidone was 1 ml:20 mg.

[0020] Preferably, the particle size of the prepared PVP-CuS NPs is 45-50 nm.

[0021] Preferably, in step (2), the mass ratio of 2-methylimidazole to PVP-CuS NPs is 6:1, and the particle size of the synthesized CuS@ZI F-8 is about 180 nm.

[0022] The second aspect of the embodiment of the present invention provides the use of the prepared nano drug delivery carrier in preparing a nano drug delivery system and preparing a drug for treating breast cancer.

[0023] A third aspect of an embodiment of the present invention provides a drug for treating breast cancer, wherein the drug is FA-RBCM-CuS / DOX@ZIF-8.

[0024] The fourth aspect of the embodiment of the present invention provides a method for preparing a drug, the process is: take 20 mg CuS@ZIF-8 and disperse it in 2 mL PBS solution, after ultrasonication for 0.5 h, add 2 mL (5 mg / mL) DOX solution, stir at 37 ° C for 24 h, after the reaction is completed, add 1 mL FA-RBCM and continue stirring for 24 h, finally centrifuge at 12000 rpm for 10 min, then wash three times with 10 mL PBS, collect the precipitate and freeze-dry it to obtain FA-RBCM-CuS / DOX@ZIF-8.

[0025] It can be seen from the above technical scheme that compared with the prior art, the present invention uses Zn-based MOF-ZIF-8 as the basic material and FA-functionalized RBCM to coat it, and develops a green bionic hybrid nanocarrier for the co-delivery of DOX and CuS NPs. Its preparation process is simple, the obtained sample particle size distribution is uniform, and the physicochemical properties are stable. The carrier has high encapsulation rate and loading capacity for DOX, has responsive drug release ability in a simulated tumor microenvironment, and has good biosafety. The presence of FA-RBCM can increase the uptake efficiency of MCF-7 cells, and the carrier can carry DOX and CuS NPs into tumor cells, exert PTT and CDT effects under NIR irradiation, induce the generation of a large amount of ROS, and achieve synergistic anti-tumor. Therefore, FR-CuS / DOX@ZIF-8 is an efficient drug delivery system with significant development and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0027] Figure 1 The attached figure is the particle size distribution diagram of different nano samples.

[0028] Figure 2 The attached figure shows the potential diagram of different nanosamples.

[0029] Figure 3 The attached figures are transmission electron microscopy images of different samples. A: CuS NPs, B: ZIF-8, C: CuS@ZIF-8, D: RBCM-CuS / ZIF-8.

[0030] Figure 4 The attached figures are scanning electron micrographs of different samples. A: ZIF-8, B: CuS@ZIF-8, C: RBCM-CuS / ZIF-8.

[0031] Figure 5 The attached figure is the ultraviolet absorption spectra of different nano samples.

[0032] Figure 6 The attached figure shows the infrared absorption spectra of different nano-samples. A: infrared spectrum of nano-materials before drug loading B: infrared spectrum of each nano-material after drug loading.

[0033] Figure 7 The attached figure shows the N2 adsorption curves of different nanoparticles.

[0034] Figure 8The attached figure shows the XPS curves of different nanosamples.

[0035] Fig. 9 The attached figure shows the XRD patterns of different nanosamples.

[0036] Fig.10 The attached figure is the DSC curve diagram of different nano samples.

[0037] Fig.11 The attached figure is the fluorescence image of FA-RBCM.

[0038] Fig.12 The attached figure shows the in vitro release curve of FA-RBCM-CuS / DOX@ZIF-8 in simulated photothermal and tumor environments.

[0039] Fig.13 The attached figure shows the results of the cytotoxicity (MCF-7) test of each nanomaterial. A: 24h, B: 48h.

[0040] Fig.14 The attached figure shows the results of the cytotoxicity (L-02) test of each nanomaterial. A: 24h, B: 48h.

[0041] Fig.15 The attached figures are the results of the cytotoxicity (MCF-7) assay of each drug delivery system. A: 24h, B: 48h, C: 24h+NIR, D: 48h+NIR.

[0042] Fig.16 The attached figure is a photothermal verification diagram of the carrier.

[0043] Fig.17 The attached figure is a graph showing the relationship between the photothermal conversion efficiency of the carrier and time.

[0044] Fig.18 The attached figures are the results of CDT effect verification of nano-samples. A: Catalytic efficiency of samples at different concentrations; B: Catalytic efficiency of samples at different pH; C: Full wavelength scanning.

[0045] Fig.19 The attached figure shows the cellular uptake diagram (fluorescence photograph) of each nanosample. A: 4h; B: 24h.

[0046] Fig. 20 The attached figure is a diagram of the reactive oxygen species (ROS) detection results (fluorescence photograph). DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Summary of sample names and abbreviations: CuS@ZIF-8(CZ), DOX@ZIF-8(ZD), CuS / DOX@ZIF-8(CZD), FA-RBCM-CuS / DOX@ZIF-8(FRCZD).

[0049] Example 1 Preparation of hybrid bionic nano drug delivery carrier FA-RBCM-CuS@ZIF-8

[0050] Step 1. Preparation of CuS NPs: Weigh 20 mg of cupric chloride dihydrate (CuCl2·2H2O) and 100 mg of polyvinyl pyrrolidone, disperse them with 5 mL of ultrapure water respectively, add them to a round-bottom flask containing 90 mL of ultrapure water, stir at 400 rpm for 1 h at room temperature, add 1 mL of sodium sulfide nonahydrate (Na2S·9H2O) dissolved in ultrapure water, stir for 5 min, transfer to an oil bath, heat at 90°C for 40 min (the solution turns dark green), after the reaction is completed, centrifuge at 12000 rpm for 20 min in a high-speed centrifuge, collect the precipitate and freeze it in a -80°C refrigerator for 12 h, and obtain it after freeze-drying.

[0051] Step 2, preparation of ZIF-8: Weigh 48 mg of 2-methylimidazole and dissolve it in 5 mL of methanol, take 4 mg of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and dissolve it in 5 mL of methanol, mix them by ultrasonic, then slowly add the methanol solution of Zn(NO3)2·6H2O to the 2-methylimidazole solution, and stir at 400 rpm for 1 hour at room temperature (the solution turns milky white). After the reaction is completed, centrifuge at 12000 rpm for 20 minutes in a high-speed centrifuge, collect the precipitate and freeze it in a -80°C refrigerator for 12 hours, and then freeze it to obtain the product.

[0052] Step 3, preparation of CuS@ZIF-8: Weigh 8 mg of the CuS NPs prepared in step 1 and dissolve them in 2 mL of methanol for ultrasonic homogeneity, weigh 16 mg of the ZIF-8 prepared in step 2 and dissolve them in 6 mL of methanol for ultrasonic homogeneity, mix the prepared CuS NPs solution with the ZIF-8 solution, add 6 mL of methanol for ultrasonic homogeneity, stir at 400 rpm for 5 min at room temperature and let stand for 2.5 h. After the reaction is completed, centrifuge at 12000 rpm for 20 min in a high-speed centrifuge, collect the precipitate and freeze it in a -80 ° C refrigerator for 12 h, and then freeze it to obtain the product.

[0053] Step 4, preparation and storage of RBCM: First, whole blood was obtained through the mouse sinus, and fresh blood was collected in a blood collection tube coated with sodium heparin. The blood was centrifuged at 1500rpm for 10min at 4°C to separate the plasma, and washed with PBS / normal saline several times until the supernatant was colorless to obtain red blood cells (RBC); the RBC was dissolved in 50mL ultrapure water and placed in a -80°C refrigerator, and repeatedly frozen and thawed to ensure that the RBC was fully burst. Subsequently, hemoglobin was removed by centrifugation at 15000rpm for 5min, and the RBCM was washed with ultrapure water several times, and filtered in sequence using 0.45μm and 0.2μm filters until the supernatant was colorless and the precipitate was light pink. The collected red blood cell ghosts were ultrasonically treated for 5min at 12% power using an ultrasonic cell disruptor, with 3s on and 2s off. The obtained RBCM was dispersed in ultrapure water containing a small amount of protease inhibitors and stored in a -80°C refrigerator.

[0054] Step 5. Preparation and storage of FA-RBCM: Weigh 10 mg of DSPE-PEG2000-FA, dissolve it in dimethyl sulfoxide by ultrasonication, mix it with 500 μL of RBCM prepared in step (4), shake it in an oscillator at 37°C in the dark for 3.5 h, and place it at 4°C for 48 h.

[0055] Step 6. Preparation of FA-RBCM-CuS@ZIF-8: Weigh 20 mg of CuS@ZIF-8 obtained in step (3), dissolve it in 2 mL of ultrapure water, mix it with the FA-RBCM in step (5), and extrude it 10 times through an Avanti micro extruder (Avanti PolarLipids) with a 200 nm and 100 nm polycarbonate membrane to obtain hybrid nanoparticles.

[0056] Example 2: Loading DOX with the carrier prepared in Example 1

[0057] Preparation of DOX@ZIF-8: 20 mg of ZIF-8 prepared in Example 1 was dispersed in 2 mL of PBS solution. After ultrasonication for 0.5 h, 2 mL (5 mg / mL) of DOX solution was added and stirred at 37 °C for 24 h. After the reaction was completed, centrifuged at 12000 rpm for 10 min and washed three times with 10 mL of PBS. The precipitate was collected and freeze-dried to obtain DOX@ZIF-8.

[0058] Preparation of CuS / DOX@ZIF-8: 20 mg of the CuS@ZIF-8 prepared in Example 1 was dispersed in 2 mL of PBS solution. After ultrasonication for 0.5 h, 2 mL (5 mg / mL) of DOX solution was added and stirred at 37 °C for 24 h. After the reaction was completed, centrifuged at 12000 rpm for 10 min and washed three times with 10 mL of PBS. The precipitate was collected and freeze-dried to obtain CuS / DOX@ZIF-8.

[0059] Preparation of FA-RBCM-CuS / DOX@ZIF-8: 20 mg of CuS@ZIF-8 prepared in Example 1 was dispersed in 2 mL of PBS solution. After ultrasonication for 0.5 h, 2 mL (5 mg / mL) of DOX solution was added and stirred at 37 °C for 24 h. After the reaction was completed, 1 mL of FA-RBCM was added and stirring was continued for 24 h. Finally, centrifugation was performed at 12000 rpm for 10 min, and then washed three times with 10 mL of PBS. The precipitate was collected and freeze-dried to obtain FA-RBCM-CuS / DOX@ZIF-8.

[0060] The loading efficiency was determined using the DOX-loaded nanosamples provided above - DOX@ZIF-8, CuS / DOX@ZIF-8, and FA-RBC M-CuS / DOX@ZIF-8. Take each nanoformulation, measure the volume of the supernatant after centrifugation, and perform the determination by HPLC. Methanol, acetonitrile, and phosphoric acid were prepared in a certain proportion as the mobile phase. DOX has strong ultraviolet absorption at 480nm, so 480nm was selected as the detection wavelength of DOX. Prepare DOX solutions of various standard concentrations for the establishment of a standard curve; then substitute the peak area A into the standard curve to determine the DOX content in the supernatant. Calculate the encapsulation efficiency and drug loading of DOX according to the formula:

[0061] Drug loading = drug amount (loaded) / nanocarrier mass

[0062] Encapsulation efficiency = drug amount (encapsulated) / total drug amount × 100%

[0063] The drug loading rate and encapsulation efficiency of each nanoformulation are shown in Table 1.

[0064] Table 1 Results of drug loading and encapsulation efficiency of different nanoformulations

[0065] Drug loading (ug / mg) Encapsulation rate (%) DOX@ZIF-8 326.8 98 CuS / DOX@ZIF-8 282.7 84.8 FR-CuS / DOX@ZIF-8 266.1 79.8

[0066] The drug loading amounts (μg / mg) of ZIF-8, CuS@ZIF-8, and FR-CuS@ZIF-8 were 326.8, 282.7, and 266.1, respectively, and the encapsulation rates were 98%, 84.8%, and 79.8%, respectively. The constructed ZIF-8 nanosystem did not significantly reduce the drug loading amount and encapsulation rate due to the increase of the modified components. Therefore, the FR-CuS@ZIF-8 in the present invention has a higher drug loading amount and encapsulation rate.

[0067] Each carrier ZIF-8, CuS NPs, CuS@ZIF-8, CuS / DOX@ZIF-8, and FR-CuS / DOX@ZIF-8 were dispersed in deionized water, and the particle size and Zeta potential of the samples were measured by a laser particle size analyzer. The results are shown in Figure 1 and Figure 2 .

[0068] Figure 1 is the particle size distribution diagram of different nanoparticles, Figure 1 It can be seen that the synthesized ZIF-8 has excellent dispersibility and a small particle size. The particle size of the drug-loaded nanoparticles is stably maintained between 250-280nm, and the particle size of the nanosystem coated with FA-RBCM is about 300nm. This particle size makes it easy for the nanocarrier to be taken up by tumor cells, thereby exerting therapeutic effects.

[0069] Figure 2 is the Zeta potential diagram of different nanoparticles, Figure 2 It can be seen that the charge of ZIF-8 is +23.1 mV, and the potential drops to +11.9 mV after encapsulating CuS NPs. DOX is positively charged, and the potential of CuS / DOX@ZIF-8 loaded with DOX rises to +15.9 mV. Both FA and RBCM are negatively charged. After coating with FA-RBCM, the potential of the hybrid nanodrug delivery system remains at around +2.4 mV and has relatively high stability.

[0070] Example 3 Sample Characterization

[0071] The samples provided in Example 1 and Example 2 - ZIF-8, CuS NPs, CuS@ZIF-8, CuS / DOX@ZIF-8, FR-CuS / DOX@ZIF-8, FA-RBCM, etc., were characterized by FT-IR, UV-Vis, TEM, SEM, XPS, etc.

[0072] The projection electron microscopy images of CuS NPs, ZIF-8, CuS@ZIF-8, and RBCM-CuS@ZIF-8 were analyzed. Figure 3 , Figure 3As shown in A in the figure, CuS NPs appear as relatively uniform small particles that are approximately spherical, with a particle size of 50-60 nm. Figure 3 As shown in Figure B, ZIF-8 has excellent dispersibility and stability, its size is stable at 160-200nm, and it presents a uniform hexagonal structure with a large space inside to load DOX. Figure 3 As shown in Figure C, the size of CuS@ZIF-8 is 160-200 nm, and it can be clearly seen that it is loaded with smaller CuS NPs, indicating that the CuS NPs are successfully anchored inside ZIF-8. Figure 3 As shown in D, the size of RBCM-CuS@ZIF-8 is 280-300nm, and there is a fuzzy film on the surface, indicating that RBCM is successfully coated on the ZIF-8 surface.

[0073] Scanning electron microscopy analysis of ZIF-8, CuS@ZIF-8, and RBCM-CuS@ZIF-8 was performed. Figure 4 , Figure 4 As shown in A, ZIF-8 has a smoother surface and a more regular shape. Figure 4 As shown in B, a part of small particles are attached to the surface of CuS@ZIF-8. During the preparation process, CuS NPs are not only embedded inside, but also adsorbed on the surface of ZIF-8. Moreover, because of the use of PVP, CuS@ZIF-8 mostly exists in the form of several aggregates. Figure 4 As shown in Figure C, RBCM-CuS@ZIF-8 becomes smoother and more transparent due to the thin layer of red blood cell membrane on the surface.

[0074] The ultraviolet absorption spectra of CuS NPs, CuS@ZIF-8 and CuS / DOX@ZIF-8 were analyzed. Figure 5 The ultraviolet absorption of CuS NPs is between 1000 and 1100 nm, and that of CuS@ZIF-8 is also in the same region, indicating that CuS NPs are successfully doped inside and on the surface of ZIF-8. The absorption peak of CuS / DOX@ZIF-8 is at 540 nm, which is due to the interaction between DOX and metal ions (Cu 2+ ) caused a red shift, demonstrating the successful loading of DOX.

[0075] Infrared absorption spectra of CuS@ZIF-8, ZIF-8, FA-RBCM, CuS / DOX@ZIF-8, and FR-CuS / DOX@ZIF-8 were analyzed. Figure 6 , Figure 6 A in the figure is the infrared absorption spectrum of CuS@ZIF-8 and ZIF-8, with the scanning wave number range of 500-4000cm -1, the X-axis represents the transmittance (%), and the Y-axis represents the wave number, the unit is cm -1 As can be seen from the figure, the peak shapes of the two are basically the same, indicating that the structure of the parent ZIF-8 is not destroyed in the further synthesis, highlighting the stability of ZIF-8. CuS@ZIF-8 has a peak shape of 1671cm -1 There is an absorption peak at , which is caused by the stretching vibration of the ortho-hydroxyl group of the benzene ring of PVP-CuS, indicating that CuS NPs are successfully anchored inside ZIF-8. Figure 6 B in the figure is the infrared absorption spectra of FA-RBCM, CuS / DOX@ZIF-8, and FR-CuS / DOX@ZIF-8. It can be seen from the figure that CuS / DOX@ZIF-8 has an infrared absorption spectrum of 2924 cm -1 There is a -CH2- stretching vibration peak at 1730cm -1 There is a C=O vibration peak at 991cm -1 There is a CH vibration peak at 2850cm -1 The emergence of antisymmetric stretching vibration peaks indicated the successful coating of FA-RBCM.

[0076] The adsorption of the nanoparticles prepared in Example 1 before and after drug loading was determined by nitrogen adsorption. Figure 7 It can be seen that the specific surface area of ​​ZIF-8 is 1091.3m 2 / g, the internal surface area is large; after the CuS NPs are anchored inside, the specific surface area becomes 484.7m 2 / g, indicating that a considerable portion of CuS NPs are embedded inside; the specific surface area of ​​FR-CuS / DOX@ZIF-8 is 93.4 m 2 / g, and the internal surface area was further reduced, which proved that a considerable part of DOX was successfully loaded inside ZIF-8, and also indicated the successful coating of RBCM, proving that ZIF-8 nanoparticles are a carrier with excellent drug loading performance.

[0077] XPS Survey spectra analysis of different nano-samples, see Figure 8 It is known that the main components of ZIF-8 are C, N, and O. All samples have C1s peak, N1s peak, and O1s peak, which proves that the synthesis of ZIF-8 is successful. CuS@ZIF-8 and FR-CuS@ZIF-8 have obvious Cu2p peaks at the binding energy of 930-940eV, which proves that CuS NPs are successfully embedded in ZIF-8 and the composite nanocarrier is successfully constructed.

[0078] XRD patterns of different nano-samples are analyzed. Fig. 9Most of the diffraction peaks of ZIF-8 and CuS@ZIF-8 are consistent, indicating that the internal embedding of CuS NPs does not affect the crystal form of ZIF-8. The characteristic diffraction peaks of CuS@ZIF-8 at 47.5° and 59.4° indicate that CuS NPs are embedded in ZIF-8.

[0079] DSC spectra of different nano-samples are analyzed. Fig.10 As can be seen from the figure, the glass transition temperature of each nanosample is low, indicating that its stability is high. Using ZIF-8 as the basic skeleton as a drug carrier, embedding CuS NPs inside and coating RBCM will not affect the stability.

[0080] Fluorescence image analysis of FA-RBCM for different nano-samples, see Fig.11 RBCM was labeled with DiD and FA was labeled with FITC. After the two were treated at 37°C and 4°C, images were taken using a fluorescence microscope. As can be seen from the figure, RBCM showed red light, FA showed green light, and the two were fused to light yellow, indicating that FA was coated on the surface of RBCM.

[0081] Based on the above characterization results, it can be seen that the present invention successfully prepared the ZIF-8 nanocarrier that can load CuS NPs and DOX, and functionalized it with FA after coating RBCM. The final nanosystem has good physical stability and biomimetic properties, good dispersibility, and has the potential to be used as an excellent delivery carrier for anti-tumor drugs.

[0082] Example 4 Release of DOX from FR-CuS / DOX@ZIF-8 in simulated in vivo environment and under photothermal action

[0083] 3 mg FR-CuS / DOX@ZIF-8 was dispersed in 3 ml PBS buffer solution of corresponding conditions (pH 7.4, pH 5), and the above liquids were placed in dialysis bags with a molecular weight cutoff of 3500Da, and then placed in the corresponding 30 mL PBS buffer solution. The mixture was continuously shaken in a constant temperature shaker at 37°C. The NIR group was irradiated with a 1064 nm laser for 5 min at regular intervals. At 1, 2, 4, 6, 8, 10, 12, 24, 36, 48, 60, 72, 84, and 96 h, 2 ml of the release liquid was drawn into a 5 mL centrifuge tube, and 2 ml of the PBS buffer of the corresponding conditions was supplemented. The peak area of ​​the release liquid at different time periods was determined by high performance liquid chromatography, and the cumulative release rate of DOX was calculated according to the standard curve of DOX. The graph was plotted with time as the horizontal axis and the cumulative release rate as the vertical axis. Fig.12It can be seen that FR-CuS / DOX@ZIF-8 has the fastest release rate under the conditions of NIR and pH 5.0, with a release rate of 67.7% in 24 hours, and then the release rate continues to grow steadily, and the release rate reaches 81% in 96 hours. In the absence of NIR and pH 7.4, the release rate is the slowest, tends to be stable in 12 hours, and the release rate is only 17.3% in 96 hours. The above results show that photothermal effect and the slightly acidic environment of tumors can promote the drug release of nano drug delivery systems.

[0084] Example 5

[0085] The cytotoxicity of each nanocarrier (material) to MCF-7 and L-02 cells and the cytotoxicity of each drug delivery system to MCF-7 were investigated by MTT method, and the concentration was used as the horizontal axis and the cell survival rate was used as the vertical axis. The survival rate of each carrier on MCF-7 cells is shown in Fig.13 The survival rate of each vector on L-02 cells is shown in Fig.14 The effects of different drug delivery systems on the survival rate of MCF-7 cells are shown in Fig.15 .

[0086] contrast Fig.13 A and Fig.13 As shown in B, when the concentration of ZIF-8, CuS NPs, CuS@ZIF-8, FR-CuS@ZIF-8 and other materials was 0-100 μg / mL, the cell survival rates for 24h and 48h were all above 80%, and the biosafety of the nanocarriers was relatively high.

[0087] Depend on Fig.14 It can be seen that compared with MCF-7 cells, the survival rate of L-02 cells was higher after being treated with different concentrations of nanomaterials for 24h or 48h, indicating that each nanomaterial basically did not affect the growth of normal cells and had good biosafety. The hybrid nanocarrier coated with RBCM had better biocompatibility.

[0088] Depend on Fig.15 A and Fig.15 As shown in B, the cytotoxicity of each nano-drug delivery system increases with the increase of concentration. The survival rate of the free DOX group is 73%, and the survival rate of the FR-CuS / DOX@ZIF-8 group is 58%. At 48h, the survival rate of the FR-CuS / DOX@ZIF-8 group drops to 53%. Fig.15 C and Fig.15As can be seen from D in the figure, under NIR irradiation, the cell survival rate further decreased, especially 48 hours after administration and under NIR irradiation, the cell survival rate of the FR-CuS / DOX@ZIF-8 group was only 36%, while the survival rate of the free DOX group was still close to 70%, indicating that the constructed nanodrug delivery system FR-CuS / DOX@ZIF-8 has a good killing effect on MCF-7 cells.

[0089] Example 6

[0090] Verification of photothermal effect: With time as the horizontal axis and temperature as the vertical axis, a temperature curve of the carrier was drawn. According to the determined concentration, ZIF-8, CuS NPs, CuS@ZIF-8, FR-CuS@ZIF-8, and water were prepared. Fig.16 As can be seen from the figure, the highest temperature of water is stable at about 27°C within 5 minutes, and the highest temperature of ZIF-8 is stable at about 30°C within 5 minutes. The temperature of CuSNPs increases gradually with the extension of illumination time, rising to about 50°C within 30 seconds, and the photothermal conversion performance is good. CuS@ZIF-8 and FR-CuS@ZIF-8 can also approach 50°C within 5 minutes and gradually stabilize. The results show that CuS NPs have good photothermal effect, and ZIF-8 loaded with CuS and surface coated with RBCM do not affect its photothermal effect.

[0091] Verification of the relationship between carrier photothermal conversion efficiency and time: ZIF-8, CuS NPs, CuS@ZIF-8, and FR-CuS@ZIF-8 were prepared into 30 μg / mL solutions and heated at 2 W / cm 2 Under the NIR irradiation condition, the infrared thermal imager was used to take pictures every 30 seconds. Fig.17 ,The results show that when the power is constant, the photothermal conversion effect of the nanosample increases with time and the temperature increases accordingly, which proves that the nanocarrier has a good photothermal conversion effect and is time-dependent.

[0092] Verification diagram of the photodynamic chemical effect of FR-CuS@ZIF-8: Samples of different concentrations were reacted with MB, H2O2, and PBS solutions, and the absorbance at 652nm was recorded every 10 minutes. Since the nanomaterial can catalyze the excess H2O2 to generate ·OH, which makes MB fade, the CDT effect of the nanocarrier is verified. Fig.18 ,Depend on Fig.18 As shown in A, with the increase of concentration, the degradation rate of MB is also accelerating. When the concentration increases to above 100 μg / mL, the degradation rate of MB reaches more than 30%. Fig.18From Figure B, we can see that pH affects the degradation rate of MB by FR-CuS@ZIF-8. When the pH is 7.4, 6.5, and 5 and the catalytic time is 60 min, the degradation rates of MB reach 87%, 61%, and 49%, respectively, indicating that pH 5 is the optimal pH condition for FR-CuS@ZIF-8 to catalyze the degradation of MB. Fig.18 C in the figure is a full wavelength scan under different pH conditions under 60 min catalysis. It can be seen from the figure that as the pH decreases, the absorption peak of MB also decreases, indicating that the MB degradation rate increases. The above results show that the CDT effect of the nanocarrier is dependent on time, concentration, and pH.

[0093] Example 7

[0094] Fluorescence localization method was used to analyze the uptake of each nanosample by MCF-7 cells. The groups were set as DOX (Control), DOX@ZIF-8, CuS / DOX@ZIF-8, FR-CuS / DOX@ZIF-8, and FR-CuS / DOX@ZIF-8+NIR. Each sample was prepared at 5 μg / mL. At this concentration, it was co-incubated with MCF-7 cells in a six-well plate for 4 hours and 24 hours. After the incubation, the culture medium was discarded, and the cells were washed twice with 1 mL of PBS. 1 mL of nuclear stain (Hoechst 33342) was added for staining for 15 minutes. After the staining, the staining solution was discarded, and the cells were washed twice with 1 mL of PBS. 1 mL of PBS solution was added to keep the cells moist, and the cell uptake was observed under a fluorescence microscope. Cell uptake fluorescence is shown in Fig.19 The results showed that the fluorescence intensity caused by the use of nanocarriers to deliver DOX was significantly higher than that of the control group (free DOX). As the surface modification of the carrier increased, the red fluorescence belonging to DOX gradually increased, and the overlap with the blue fluorescence of the cell nucleus increased, indicating that nanocarriers can significantly improve the cellular uptake rate of chemotherapeutic drugs and have excellent delivery performance. NIR irradiation can enhance the uptake rate of hybrid carriers.

[0095] Nano-samples induced cells to produce ROS results verification:

[0096] Fluorescence localization method was used to analyze the effect of each nanosample in inducing ROS production in MCF-7 cells. The groups were Control, DOX, DOX@ZIF-8, CuS / DOX@ZIF-8, FR-CuS / DOX@ZIF-8, and FR-CuS / DOX@ZIF-8+NI R. Each sample was configured at 5 μg / mL. At this concentration, it was co-incubated with MCF-7 cells in a six-well plate for 4 h and 24 h. After the incubation, the culture medium was discarded, washed twice with 1 mL PBS, and 1 mL of ROS fluorescent probe was added for staining for 15 min. After the staining, the staining solution was discarded, washed twice with 1 mL PBS, and 1 mL PBS solution was added to keep the cells moist. The generation of ROS in the cells was observed under a fluorescence microscope. The results are shown in Fig. 20 As shown in the figure, compared with free DOX, the drug delivery system can induce the production of ROS more efficiently. The amount of intracellular ROS generated by the hybrid drug delivery system is higher. After NIR irradiation, the intracellular ROS level increases to a certain extent. This result shows that FR-CuS / DOX@ZIF-8 can effectively deliver drugs into cells and induce the production of a large amount of ROS to achieve synergistic treatment.

[0097] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0098] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A hybrid bionic RBCM / Zn-MOF nano drug delivery carrier, characterized in that: The nano drug delivery carrier is FA-RBCM-CuS@ZIF-8.

2. The method for preparing the nano drug delivery carrier according to claim 1, characterized in that: The process includes: (1) synthesis of PVP-CuS NPs; (2) Synthesis of CuS@ZIF-8: 2-Methylimidazole was mixed with PVP-CuS NPs, and zinc nitrate hexahydrate was added and mixed again to prepare the pH-responsive nanocarrier CuS@ZIF-8; (3) FA is connected to the surface of RBCM to obtain FA-RBCM, and mixed with the CuS@ZIF-8 prepared in step (2), and extruded to obtain FA-RBCM-CuS@ZIF-8 nano drug delivery carrier.

3. The preparation method according to claim 2, characterized in that: In step (1), the specific process of synthesizing PVP-CuS NPs is as follows: Copper chloride dihydrate and polyvinyl pyrrolidone were weighed in a mass ratio of 1:5, dispersed in ultrapure water, stirred at room temperature for 1 hour, sodium sulfide nonahydrate was added, stirred for 5 minutes, transferred to an oil bath, heated at 90°C for 40 minutes. After the reaction was completed, centrifuged, the precipitate was collected and freeze-dried to synthesize PVP-CuS NPs; wherein the volume mass ratio of sodium sulfide nonahydrate to polyvinyl pyrrolidone was 1 ml:20 mg.

4. The preparation method according to claim 3, characterized in that: The particle size of the prepared PVP-CuS NPs is 45-50 nm.

5. The preparation method according to claim 4, characterized in that: In step (2), the mass ratio of 2-methylimidazole to PVP-CuSNPs is 6:1, and the particle size of the synthesized CuS@ZIF-8 is about 180 nm.

6. Use of the nano drug delivery carrier prepared by the preparation method according to any one of claims 2 to 5 in preparing a nano drug delivery system and a drug for treating breast cancer.

7. A drug for treating breast cancer, characterized in that: The drug is FA-RBCM-CuS / DOX@ZIF-8.

8. The method for preparing the drug according to claim 7, characterized in that: The process is as follows: 20 mg CuS@ZIF-8 is dispersed in 2 mL PBS solution, and after ultrasonic treatment for 0.5 h, 2 mL 5 mg / mL DOX solution is added, and stirred at 37 °C for 24 h. After the reaction is completed, 1 mL FA-RBCM is added and continued to stir for 24 h. Finally, centrifuge at 12000 rpm for 10 min, and then wash three times with 10 mL PBS. The precipitate is collected and freeze-dried to obtain FA-RBCM-CuS / DOX@ZIF-8.

Citation Information

Patent Citations

  • Red cell membrane base-polydopamine nano delivery carrier and preparation method thereof

    CN117797121A

  • Inflammatory macrophage and osteoclast dual-targeting bionic nanocomposite and preparation method thereof

    CN118453904A